Hydrological balance of the Boura dam (Burkina Faso) - Fowe, T.; Karambiri, H.; Poussin, Jean-Christophe; Checchi, P; Paturel, J.E. (CGIAR Challenge Program on Water and Food, 2013)
In developing countries, where many basins are ungauged or poorly gauged, small reservoirs could be used as hydrometric stations for estimating runoff of small watersheds upstream of the dams. Thus, hydrological monitoring of dam is essential in water resources management by predicting where there may be shortages or surplus water.